A Global Overview of Male Escort Websites. Issue 12 (15th October 2017) - Kumar, Navin; Minichiello, Victor; Scott, John; Harrington, Taylor
ABSTRACT: This article details a preliminary dataset of global male escort sites to give insight into the scale of the online market. We conducted a content analysis of 499 Web sites and also measured traffic to these sites. Our analysis examined the structural characteristics of escort services, geographical and regulatory contexts, and resilience of such services. Results suggest that most sites are independent and not affiliated to escort agencies, and the majority cater to male escorts soliciting male clients, with a number of sites for female clientele and couples. These Web sites are dispersed globally, with Asian, European, and South American countries the major hubs in the market and a small number of large multinational sites based in the United States and Europe figuring as a major presence in markets. Although still subject to high levels of regulation in many parts of the world, the data suggest that male escorting is becoming more visible in diverse cultural contexts as measured by the number of Web sites appearing in public spaces.